P240Use of IL-10 overexpressing macrophages for targeted anti-inflammatory therapy in humans - benefit of the M2 polarization?. (15th July 2014) - Zimmermann, O; Homann, J; Bangert, A; Rottbauer, W; Torzewski, J; Katus, H; Lorenz, HM; Kaya, Z
Abstract: Purpose: Inflammatory diseases like rheumatoid arthritis or myocarditis represent therapeutic challenges. Systemic and non-directional immunosuppressive therapy is related with side effects. Macrophages specifically target inflammatory tissues. Interleukin-10 (IL-10) is a potent anti-inflammatory cytokine. Thus, overexpression of IL-10 in macrophages could result in a targeted and highly efficient therapeutic effect. We already could apply this therapy successfully in a murine model of autoimmune myocarditis. Now this approach should be transferred to human macrophages. Methods: Human macrophages were isolated from buffy coats. Using magnetically labelled antibodies against CD3, CD7, CD16, CD19, CD56, CD123 and Glycophorin A finally CD14-positive cells were negative selected. FACS against CD14 and CD16 characterized the target cells. After 7 days in culture (RPMI 1640, 20% FCS; M1: 200 U/ml GM-CSF; M2: 100 ng/ml M-CSF) cells differentiated to macrophages. M1 polarization was induced by culture in RPMI 1640, 5% FCS, 100 ng/ml LPS and 20 ng/ml interferon-gamma. M2 polarization was induced by RPMI 1640, 5% FCS and 20 ng/ml IL-4. mRNA-nucleofection was used for overexpression of IL-10. Production of IL-10, TNF-alpha and IL-6 were detected in the supernatant by ELISA. Results: Isolated cells were identified as human macrophages. After IL-10 overexpression a significant increase of IL-10 was detected compared with the control (50 pg/ml vs. 220 pg/ml). IL-6 (14 pg/ml vs. 26 pg/ml) and TNF-alpha (18 pg/ml vs. 26 pg/ml) showed a low concentration without relevant differences to the control. The M1 population was characterized by a spontaneous IL-10 concentration of 183 pg/ml. mRNA-nucleofection could not increase this amount significantly (215 pg/ml). Spontaneous expression of IL-6 and TNF-alpha was high with 630 pg/ml and 1000 pg/ml, respectively. The M2 population presented with a low spontaneous production of IL-10 (51 pg/ml), but concentrations for IL-6 (15 pg/ml) and TNF-alpha (10 pg/ml) were even lower. After overexpression of IL-10 a nearly 10-fold increase of IL-10 was detected (472 pg/ml). Conclusions: M2 polarization of human macrophages is characterized by low inflammatory markers. Here the highest overexpression of IL-10 could be achieved. In contrast the M1 population presents pro-inflammatory with high IL-6 and TNF-alpha levels. Here only a low overexpression of IL-10 is possible. As nucleofection is according to the GMP guidelines an in vivo application of this therapeutic approach in humans seems feasible. By use of the M2 polarization anti-inflammatory effects could be increased.